Optimal growth, t_f, t_0 and wavenumber as function of Re_δ (Re_o=8000,A=infty) - Duo Xu; Baofang Song; Marc Avila (PANGAEA, 2022)
The data are obtained via an in-house Matlab script (developed by Dr. Baofang Song) to compute the non-modal transient growth of disturbances in pulsatile and oscillatory pipe flows. In this study, a Newtonian fluid driven by pulsatile and oscillatory flow rate flows in a straight pipe. In pulsatile flow, there are three governing parameters: steady Reynolds number (defined by the steady flow component), pulsation amplitude (ratio of oscillatory and steady flow component) and Womersley number (dimensionless pulsation and oscillation frequency). In oscillatory flow, due to vanishment of steady flow component, oscillatory Reynolds number (defined by the oscillation flow component) and Womersley number. The Reynolds number defined by the thickness of Stokes layer is alternatively used for the oscillatory Reynolds number. The study was carried out in a manner that one governing parameter varies while other governing parameters are fixed. The data file extquotesingleTG_t0_tf_wavenumber_Redelta_Reo8000.dat extquotesingle shows the dependence of the optimal wavenumber on the Womersley number for the oscillatory Reynolds number of 8000. This file includes twelve columns: the first column indicates the Womersley number; the second column indicates the pulsation period; the third column indicates the optimal axial wavenumber; the fourth column indicates the optimal azimuthal wavenumber; the fifth column indicates the initial time of the optimal perturbation; the sixth column indicates the final time of the optimal perturbation; the seventh column indicates the evolution time of the optimal perturbation; the eighth column indicates the initial time of the optimal perturbation normalized by the pulsation period; the nineth column indicates the final time of the optimal perturbation normalized by the pulsation period; the tenth column indicates the evolution time of the optimal perturbation normalized by the pulsation period; the eleventh column indicates the maximum energy amplification; the twelfth column indicates the Reynolds number which is defined with the characteristic length of the thickness of the Stokes layer.